Relationship between negative emotions and perceived support among parents of hospitalized, critically ill children - Brad E. Phillips; Laurie A. Theeke; Katie M. Sarosi (Elsevier, 2021)
Objectives: The purpose of this study was to describe relationships between negative emotions and perceived emotional support in parents of children admitted to the pediatric intensive care unit (PICU). Methods: This cross-sectional descriptive study conducted face-to-face interviews between January 2019 and January 2020. Study variables included depression (PHQ-9 Scale), anxiety (Emotional Distress-Anxiety-Short Form 8a), anger (Emotional Distress-Anger-Short Form 5a), fear (Fear-Affect Computerized Adaptive Test), somatic fear (Fear-Somatic Arousal-Fixed Form), loneliness (Revised 20-item UCLA Loneliness Scale), and perceived emotional support (Emotional Support-Fixed Form). Results: Eighty parents reported symptoms of depression 8.00(4.00, 13.75), anxiety (23.43 ± 7.80), anger (13.40 ± 5.46), fear (72.81 ± 27.26), somatic fear 9.00(6.00, 12.75), loneliness (39.35 ± 12.00), and low perceived emotional support (32.14 ± 8.06). Parents who were young, single, low-income, and with limited-post secondary education reported greater loneliness and lower perceived emotional support. Fear correlated with depression (r = 0.737, P < 0.01) and anxiety (r=0.900, P < 0.01). Inverse relationships were discovered between perceived emotional support and loneliness (r = −0.767, P < 0.01), anger (r=-0.401, P < 0.01), and depression (r = −0.334, P < 0.01). Conclusions: The cluster of negative emotions identified will serve as potential targets for future interventions designed to enhance support for parents of critically ill children.